Monetary policy and market interest rates - Tore Ellingsen; Ulf Söderström (Sveriges Riksbank, 1998)
We investigate, theoretically and empirically, the relationship between monetary policy and the term structure of interest rates. In particular, we show in a dynamic macroeconomic model that if monetary policy reveals information about economic developments, interest rates of all maturities move in the same direction in response to a policy innovation. If, on the other hand, monetary policy reveals information about the central bank's policy preferences, short and long interest rates move in opposite directions. In the empirical section, we provide direct measures of endogenous and exogenous monetary policy innovations in the U.S. by analyzing the reaction of financial market participants to Federal Reserve policy moves. The empirical findings support the theoretical predictions.
Keywords: E43; E52; 330; Monetary policy; term structure of interest; event studies; central bank private information